Moving Pictures/Stopping Places: Hotels and Motels on Film - Clarke, David B.; Crawford Pfannhauser, Valerie; Doel, Marcus A. (Lexington Books, 2009)
Mobility has long been a defining feature of modern societies, yet remarkably little attention has been paid to the various 'stopping places'_hotels, motels, and the like_that this mobility presupposes. If the paradoxical qualities of fixed places dedicated to facilitating movement have been overlooked by a variety of commentators, film-makers have shown remarkable prescience and consistency in engaging with these 'still points' around which the world is made to turn. Hotels and motels play a central role in a multitude of films, ranging across an immensely wide variety of genres, eras, and national cinemas. Whereas previous film theorists have focused on the movement implied by road movies and similar genres, the outstanding contributions to this volume extend the recent engagement with space and place in film studies, providing a series of fascinating explorations of the cultural significance of stopping places, both on screen and off. Ranging from the mythical elegance of the Grand Hotel, through the uncanny spaces of the Bates motel, to Korean 'love motels,' the wealth of insights, from a variety of theoretical perspectives, that this volume delivers is set to change our understanding of the role played by stopping places in an increasingly fluid world.